2020
DOI: 10.1007/s13205-020-02387-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of methicillin-resistant Staphylococcus aureus through genomics approach

Abstract: In the present study, a total of 35 S. aureus isolates collected from two different geographical locations viz., Germany and Hungary were tested for their methicillin-resistant phenotype which revealed a high incidence of methicillin-resistant S. aureus. The quantitative test for biofilm production revealed that 73.3% of isolates were biofilm producers. The isolates were further characterized using a set of biochemical and genotypic methods such as amplification and analysis of S. aureus species-specific seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 129 publications
(138 reference statements)
4
21
4
Order By: Relevance
“…These genes were detected in all isolates however, the biofilm production ability varies from weak to strong were observed in our previous study ( Naorem et al, 2020 ). Our previous study identified that SA G6 isolate obtained from skin infection showed a weak biofilm-forming ability ( Naorem et al, 2020 ). The low biofilm formation in SA G6 might be degraded the biofilm by DNase enzyme found in skin cells ( Eckhart et al, 2007 ).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…These genes were detected in all isolates however, the biofilm production ability varies from weak to strong were observed in our previous study ( Naorem et al, 2020 ). Our previous study identified that SA G6 isolate obtained from skin infection showed a weak biofilm-forming ability ( Naorem et al, 2020 ). The low biofilm formation in SA G6 might be degraded the biofilm by DNase enzyme found in skin cells ( Eckhart et al, 2007 ).…”
Section: Discussionsupporting
confidence: 50%
“…The penicillin resistance gene ( blaZ ) was found absent in SA G8 isolate. This in-silico identification and our previous antibiotic susceptibility test results were correlated with beta-lactam, erythromycin (MLS), and vancomycin antibiotic resistance analysis ( Naorem et al, 2020 ). The secondary metabolite biosynthetic gene clusters identified among the genomes were staphylobactin, aureusimine, bacteriocin, and staphyloferrin A.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The S. aureus genome can encode about 2700 proteins, including cytoplasm, cell membrane, cell surface, and secreted proteins 20–22 . Among the many proteins, cell surface and secreted proteins have a high chance of being recognized by the host immune system with resultant antibodies against S. aureus 23–25 . Utilizing a multiantigen Luminex immunoassay with specific antibodies against S. aureus , the humoral immune response can be measured in chronic orthopedic infections and have shown promising value 26–28 .…”
Section: Discussionmentioning
confidence: 99%